2019
DOI: 10.3389/fmicb.2019.02637
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Infection Activates Interleukin-1β to Induce Tissue Injury and Vascular Leakage

Abstract: Dengue virus (DENV) infection causes several diseases ranging from dengue fever to life-threatening dengue hemorrhagic fever and dengue shock syndrome characterized by endothelial dysfunction, vascular leakage, and shock. Here, we identify a potential mechanism by which DENV induces tissue injury and vascular leakage by promoting the activation of interleukin (IL)-1β. DENV facilitates IL-1β secretion in infected patients, mice, human peripheral blood mononuclear cells (PBMCs), mouse bone marrow-derived macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 50 publications
2
41
1
Order By: Relevance
“…This study has shown that TNF-a, IL-1b, and IL-12 levels are significantly elevated in dengue patients compared with HCs and that these proinflammatory cytokine levels are associated with dengue severity in Vietnamese patients with dengue infection. These findings are consistent with previous studies indicating a crucial role of TNF-a, IL-1b, and IL-12 in dengue (6,16,19,20). Elevated cytokine levels may contribute to the increase of vascular permeability, initiation of coagulation, AST, aspartate aminotransferase; ALT, alanine aminotransferase; DENV, dengue virus; DWS-, dengue without warning signs; DWS+, dengue patients with warning signs; HC, healthy controls; HCT, hematocrits; IgG, Immunoglobulin G; IU, international unit; NA, not applicable; NS, not significant; NS1, nonstructural antigen 1; PLT, platelet; RBC, red blood cells; SD, severe dengue; WBC, white blood cells.…”
Section: Discussionsupporting
confidence: 93%
“…This study has shown that TNF-a, IL-1b, and IL-12 levels are significantly elevated in dengue patients compared with HCs and that these proinflammatory cytokine levels are associated with dengue severity in Vietnamese patients with dengue infection. These findings are consistent with previous studies indicating a crucial role of TNF-a, IL-1b, and IL-12 in dengue (6,16,19,20). Elevated cytokine levels may contribute to the increase of vascular permeability, initiation of coagulation, AST, aspartate aminotransferase; ALT, alanine aminotransferase; DENV, dengue virus; DWS-, dengue without warning signs; DWS+, dengue patients with warning signs; HC, healthy controls; HCT, hematocrits; IgG, Immunoglobulin G; IU, international unit; NA, not applicable; NS, not significant; NS1, nonstructural antigen 1; PLT, platelet; RBC, red blood cells; SD, severe dengue; WBC, white blood cells.…”
Section: Discussionsupporting
confidence: 93%
“…IL-1β is a homolog of IL-1α and uses the same receptor as IL-1α. Pan et al reported that DENV infection induces IL-1β secretion from macrophages in patients and mice, and IL-1β induces vascular leakage in both in vitro vascular endothelial monolayers and in mice, while IL-1Ra alleviates these IL-1β-mediated effects ( 29 ). In agreement with the above studies, the results of our work suggest that IL-1α is a crucial mediator that promotes the incidence of JE by disrupting BBB integrity at a very early stage of infection.…”
Section: Discussionmentioning
confidence: 99%
“…DENV infection mediated IL-1β activation are found in infected patient blood samples, human peripheral blood mononuclear cells (PBMCs) and monocyte-differentiated macrophages (THP-1) as well in C57BL/6 mice and mouse bone marrow derived macrophages (BMDMs). Evidence demonstrates that IL-1β augments tissue injury and leakage in IFNAR-/- C57BL/6 mice, although IL-1 receptor antagonist (IL-1RA) protects from this injury (Pan et al, 2019b ). Together, the collected results reveal the mechanism of DENV pathogenesis and establish the contribution of IL-1β in DENV-associated pathology and recommend the consideration of IL-1RA for effective therapeutics in DENV patients' treatment.…”
Section: Response Of Host Inflammasome To Denv Infectionmentioning
confidence: 99%